Incidence, Epidemiology, and Outcomes of Pediatric Tracheostomy in the United States from 2000 to 2012. (23rd October 2018) - Muller, R. Grant; Mamidala, Madhu P.; Smith, Samuel H.; Smith, Aaron; Sheyn, Anthony
Abstract : Objectives: To investigate national and regional variations in pediatric tracheostomy rates, epidemiology, and outcomes from 2000 to 2012. Study Design: Retrospective cohort analysis. Setting: Previous research with the 1997 edition of the Kids' Inpatient Database (KID), a national database of pediatric hospital discharge data, demonstrated that rates and outcomes of pediatric tracheostomy vary among US geographic regions. The KID has since been released an additional 5 times, increasing in size with successive editions. Subjects and Methods: Patients ≤18 years old with procedure codes for permanent or temporary tracheostomy from 2000 to 2012 were included. Primary outcome was a weighted population‐based rate of tracheostomy stratified by year. Secondary analysis included epidemiologic characteristics and outcomes stratified by year and geographic region. Results: A weighted total of 24, 354 cases was analyzed. Population‐based tracheostomy rates decreased from 6.8 ± 0.2 (mean ± SD) tracheostomies per 100, 000 child‐years in 2000 to 6.0 ± 0.2 in 2012. Minorities increased from 53.3% in 2000 to 56.4% in 2012. Patients experienced increased procedures, diagnoses, length of stay, and hospital charges with time. From 2000 to 2012, rates and outcomes varied by US geographic region. Mortality during hospitalization (8%) did not vary by year, patient age, region, or sex. Conclusions: Pediatric tracheostomy is associated with variation in incidence, epidemiology, and hospitalization outcomes in the United States from 2000 to 2012. While rates of pediatric tracheostomy decreased, patients became increasingly medically complicated and ethnically diverse with outcomes varying according to geographic region.